PENERAPAN MODEL PJBL BERBANTUAN MEDIA TANGRAM UNTUK MENINGKATKAN KEAKTIFAN BELAJAR MATEMATIKA SISWA KELAS IV SD - Adamus Firdaus, Al; Ika Rahayu Nita, Cicilia; Hananing Utami, Yayuk (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students’ mathematics learning activity through the implementation of Project Based Learning (PjBL) assisted by tangram media on plane geometry material in fourth-grade students at SD Negeri Sukun 1 Kota Malang. This research was conducted based on the problem of low student involvement during mathematics learning, as indicated by students’ lack of participation in asking questions, answering questions, expressing opinions, participating in discussions, and the presence of off-task activities during the learning process. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which was carried out in two cycles. The subjects of this study were 27 fourth-grade students at SD Negeri Sukun 1 Kota Malang. Data collection techniques included observation, interviews, and documentation. The data were analyzed using descriptive quantitative analysis. The results showed that the implementation of PjBL assisted by tangram media improved students’ learning activity. The percentage of students’ learning activity increased from 46% in the pre-action stage to 69% in the first cycle and reached 85% in the second cycle. Therefore, the implementation of Project Based Learning assisted by tangram media is effective in improving elementary school students’ mathematics learning activity and creating an active, meaningful, and student-centered learning process.